Effect of dietary supplementation of organic zinc on laying performance, egg quality and some biochemical parameters of laying hens. Issue 2 (9th October 2017) - Abd El‐Hack, M. E.; Alagawany, M.; Amer, S. A.; Arif, M.; Wahdan, K. M. M.; El‐Kholy, M. S.
Summary: This study was conducted to evaluate the effects of zinc methionine (Zn‐Met) supplementation on the performance, egg quality, antioxidant status and some biochemical parameters of blood serum in laying hens from 22 to 34 weeks of age. A total of 120 Hisex Brown laying hens of 22‐week‐old were randomly allocated into five treatments with six cage replicates for each (four hens/replicate). Dietary treatments consisted of the basal diet with no Zn‐Met supplementation (control group) and basal diet supplemented with 25, 50, 75 or 100 mg Zn‐Met/kg diet. No significant differences were observed on body weight, body weight gain or feed conversion ratio due to dietary Zn‐Met supplementation. However, highly significant impact was observed on daily feed intake. Egg number, egg weight and egg mass were increased in the group fed diet supplemented with the highest level of Zn‐Met (100 mg/kg of diet) as compared to other groups. All egg quality traits were statistically ( p  > .05 or .01) affected as a response to dietary Zn‐Met supplementation except egg shape index, shell percentage and yolk index. In comparison with the control group, dietary supplementation of 25, 50, 75 or 100 mg Zn‐Met/kg decreased serum triglyceride and LDL‐cholesterol levels. Serum cholesterol level was increased with all dietary levels of Zn‐Met in comparison with the control group. Dietary Zn‐Met supplementation increased the serum content of zinc, where the highest values were recorded with 50 and 100 mg Zn‐Met/kg diet. Dietary Zn‐Met levels did not affect the antioxidant indices in blood serum except for the activity of copper–zinc superoxide dismutase (Cu‐Zn‐SOD). The activity of Cu‐Zn‐SOD was increased with Zn‐Met supplementations with no differences among supplemental zinc levels. It is concluded that dietary Zn‐Met supplementation reduced serum triglyceride, LDL‐cholesterol and increased Zn status and resulted in promoting antioxidant ability of laying hens, and the addition of 100 mg Zn‐Met/kg to layer diet was appropriate for improving the above parameters in addition to egg production indices and Haugh unit score.